Antioxidants Such as Flavonoids and Carotenoids in the Diet of Bogor, Indonesia Residents - Nuri Andarwulan; Niken Cahyarani Puspita; Saraswati; Dominika Średnicka-Tober (MDPI AG, 2021)
Due to the strong antioxidant activity of flavonoids and carotenoids, daily consumption of these bioactive compounds has the potential for reducing the risk of many chronic and degenerative diseases caused by or contributed to by oxidative stress. Currently, the available research results related to the flavonoid and carotenoid intake in Asian countries are very limited, especially for Indonesian population. The present study was conducted in Bogor City and Bogor District, West Java, Indonesia. Food consumption data was obtained through the food frequency questionnaire (FFQ) method, involving 200 respondents aged 25-65 years old. Flavonoids and carotenoids contents of the consumed food items were determined by referring to the databases developed by the United States Department of Agriculture (USDA), scientific journals, and calculation based on the recipes recorded in the survey. The total flavonoid intake of Bogor adults was estimated as 149.5 mg/day, consisting of 49.4% isoflavones, 24.0% flavonols, 9.4% flavanones, 7.0% flavan-3-ols, 6.0% flavones, and 4.2% anthocyanidins, and was contributed to mainly by legumes (70.7%), vegetables (10.1%), and fruits (7.3%). At the same time, the estimated total carotenoid intake reached 7.6 mg/day, and was contributed to mainly by vegetables (53.9%), fruits (20.2%), and snacks (14.4%), with β-carotene consumed in the highest proportion (49.9%), followed by lycopene (19.9%), lutein and zeaxanthin (13.5%), α-carotene (6.9%), and β-cryptoxanthin (2.6%). The effects of different respondents' characteristics, such as area of residence (city vs. district), gender (male vs. female), and age (25-40, 41-55, and 56-65 years old) on the flavonoid and carotenoid intake varied widely, due to the differences in the overall consumption patterns of the respective respondents' groups.